A comparative systematic review and meta-analysis of uterine artery resistance in pregnant women with and without previous history of cesarean section - Arash Mohazzab; Azar Mohammadzadeh; Banafsheh Nikfar; Safdar Masoumi; Elham Shoraka; Neda Hashemi; Shahla Chaichian (PLoS ONE, 2025)
Background Increased uterine artery resistance in pregnant women with a history of cesarean section has been suggested to contribute to adverse pregnancy outcomes. However, the literature presents conflicting reports on this association. In this comparative meta-analysis and systematic review, we aimed to evaluate the studies that reported uterine artery resistance using Color Doppler ultrasonography in pregnant women with and without a history of cesarean section. Methods We searched PubMed, Scopus, Web of Science, and Embase up to April 2024 using relevant keywords. Study selection was performed by two independent researchers, with conflicts resolved by a third. Risk of bias was assessed using the Newcastle-Ottawa Scale. The primary outcomes were the Pulsatility Index (PI) and Resistance Index (RI) Meta-analysis and meta-regression were conducted using STATA version 17. Results After screening 442 articles, the meta-analysis included six studies, encompassing 1,656 participants. We found a small but statistically significant increase in uterine artery resistance, based on PI, in women with a history of cesarean section (Hedges’s g = 0.15, 95% CI [0.03, 0.26], p = 0.01). Heterogeneity among studies was low (I² = 26.60%, p = 0.23), and no significant publication bias was detected (Egger’s test, p = 0.81). Analysis of the RI, based on two studies, showed a non-significant increase in the cesarean group (Hedges’s g = 0.19, 95% CI [−0.06, 0.43], p = 0.13). Conclusion A history of cesarean section may be associated with increased uterine artery resistance. These findings suggest a possible benefit in monitoring uterine artery resistance in subsequent pregnancies, mainly using Color Doppler ultrasonography, to better understand potential risks such as preeclampsia and intrauterine growth restriction. However, given the limited evidence, further studies are warranted to confirm these associations and clarify their clinical relevance.